2020
DOI: 10.1002/bit.27330
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the oxidative stress‐mediated increase in lipid accumulation by the bacterium, R. opacus PD630: Experimental analysis and genome‐scale metabolic modeling

Abstract: Appropriate species of oleaginous bacteria, with their high growth rates and lipid accumulation capabilities, can be good contenders for industrial triacylglycerol (TAG) production, compared to microalgae. Further, oxidative stress (OS) can be used to significantly increase TAG yields in oleaginous microbes, but the mechanism is unexplored. In a first, this study explored the mechanism behind OS‐mediated increase in TAG accumulation by the bacterium, Rhodococccus opacus PD630, through experimental analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Shear stress was reported to induce apoptosis in breast cancer cells in circulation by enhancing the mitochondrial production of superoxide 22 . Moreover, it is now clear that reactive species (RS), especially the reactive oxygen species (ROS), are the molecular mediators of the effects of many stresses on cells 23,24 . Thus, we studied the effects of shear stress on si‐RS in HCT116 cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear stress was reported to induce apoptosis in breast cancer cells in circulation by enhancing the mitochondrial production of superoxide 22 . Moreover, it is now clear that reactive species (RS), especially the reactive oxygen species (ROS), are the molecular mediators of the effects of many stresses on cells 23,24 . Thus, we studied the effects of shear stress on si‐RS in HCT116 cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…22 Moreover, it is now clear that reactive species (RS), especially the reactive oxygen species (ROS), are the molecular mediators of the effects of many stresses on cells. 23,24 Thus, we studied the effects of shear stress on si-RS in HCT116 cancer cells.…”
Section: Shear Stress Increased Specific Intracellular Reactive Speci...mentioning
confidence: 99%
“…iGR1773 consists of 3025 reactions and 1956 metabolites obtained from annotating its completed genome, adding the corresponding metabolic reactions, and testing the predictions derived by it. Although previous publications have reported a GSM for R. opacus PD630, , this model did not use an annotation of the R. opacus PD630 genome. This model repurposed the Rhodococcus jostii GSM by doing some minor modifications including setting fluxes to polyhydroxyalkanoates (PHA), polyhydroxyvalerates (PHV), glycogen, and acetate to zero and adjusting the TAG reaction to reflect the fatty acid composition of R. opacus PD630 .…”
Section: Introductionmentioning
confidence: 99%
“…Although previous publications have reported a GSM for R. opacus PD630, , this model did not use an annotation of the R. opacus PD630 genome. This model repurposed the Rhodococcus jostii GSM by doing some minor modifications including setting fluxes to polyhydroxyalkanoates (PHA), polyhydroxyvalerates (PHV), glycogen, and acetate to zero and adjusting the TAG reaction to reflect the fatty acid composition of R. opacus PD630 . Notably, iGR1773 was validated in three different ways: via the Metabolic Model Test (MEMOTE) suite, by checking growth rate predictions, and by comparing flux predictions to 13 C-metabolic flux analysis ( 13 C-MFA) results.…”
Section: Introductionmentioning
confidence: 99%
“…16 Several studies on bacteria have reported that the inhibition of glycolysis allows cells to divert flux into the pentose phosphate pathway to promote NADPH synthesis and enhance the protection against oxidative stress. [17][18][19] On the other hand, B. pertussis does not have an active glycolysis pathway and instead uses gluconeogenesis to process the product of the TCA cycle that is driven by glutamate as the main nutrient. In fact, it has been shown that B. pertussis can synthesize most amino acids and grow in media containing mostly glutamate and proline which is also converted to glutamate.…”
Section: Introductionmentioning
confidence: 99%